2003
DOI: 10.1007/s00296-003-0353-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of asymptomatically poor muscle perfusion of lower extremities measured in systemic lupus erythematosus patients with abnormal myocardial perfusion

Abstract: Patients with systemic lupus erythematosus (SLE) may develop premature atherosclerosis, notably peripheral vascular disease (PVD) presenting with intermittent claudication or gangrene. Therefore, it is important to investigate if high prevalence of poor muscle perfusion of lower extremities in SLE patients with abnormal myocardial perfusion is related to more cardiovascular risk factors. We used a well-established and noninvasive radionuclide method (xenon 133 muscle washout) to evaluate objectively the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…23 Lin CC et al using xenon 133 muscle washout showed that muscle perfusion in the lower extremities of SLE patients without symptoms or signs of PVD is significantly decreased and is related to abnormal myocardial perfusion. 24 Thallium-201 muscle perfusion scans have shown reduced perfusion reserve in distal muscles in asymptomatic lupus patients. 25 We used Doppler ultrasonography since it can detect upper limb disease in addition to that of lower limbs and has the advantage of delineating structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…23 Lin CC et al using xenon 133 muscle washout showed that muscle perfusion in the lower extremities of SLE patients without symptoms or signs of PVD is significantly decreased and is related to abnormal myocardial perfusion. 24 Thallium-201 muscle perfusion scans have shown reduced perfusion reserve in distal muscles in asymptomatic lupus patients. 25 We used Doppler ultrasonography since it can detect upper limb disease in addition to that of lower limbs and has the advantage of delineating structural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] A recent study proposed that muscle perfusion in the lower extremities of SLE patients without symptoms of obliterative macrovascular disease is significantly decreased, although the nature of functional changes remains obscure. 8 On the basis of previous observations we hypothesized that SLE impairs the regulation of arteriolar resistance by affecting mechanisms intrinsic to the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Recent reports have demonstrated that in SLE patients, perfusion of cardiac and skeletal muscle is significantly reduced without the signs and symptoms of macrovascular obstruction, suggesting functional impairment of microvessels. 7,8 It is known that arterioles are primary responsible for regulation of circulatory resistance, however the nature of arteriolar dysfunction in SLE remains obscure. The clinical observations suggest that SLE induces multiple alterations in vascular function however; these alterations have not yet been characterized in microvessels.…”
Section: Introductionmentioning
confidence: 99%
“…Various modalities can be used to detect vascular disease in lupus. Theodoridou et al used an abnormal Ankle-Brachial Index, while Lin et al using xenon-133 muscle washout showed that muscle perfusion is significantly reduced in the lower extremities of patients with SLE 17 18. Thallium-201 muscle perfusion scans have also shown reduced perfusion reserve in distal muscles in asymptomatic patients with SLE 19.…”
Section: Discussionmentioning
confidence: 99%